Strengths and Challenges of Federal Governance in Nepal: Re Thinking with Rural Development Approach (Research Nepal Journal of Development Studies, 2020)
Rural development in Nepal is a complex phenomenon. It is an interaction among economic, social, political and cultural factors. The concept of rural development is a process of wholistic development and change to improve rural livelihood. Rural development is linked with infrastructural development, commercialization of agriculture, proper utilization and of resources, food security, creating opportunities, inclusive development in the rural area and positive change in overall society. The main objective of the study is to assess the strength and challenges of federal governance in Nepal. Further, the study had reviewed the existing governance status in Nepal including Local Self Governance Act (LSGA) 1999 and its impact in the country. It aims to identify the rural development approach for the proper development of the nation with need based or right based approach. The study was conducted in the descriptive and exploratory design. The secondary data were only used in the study. The major sources of data were collected from the MoFALD, Central Library of TU, CBS, CEDA library, Nepal Rasta Bank Library, NPC, Public Information Centre, World Bank, Nepal etc. Nepal is still anxious to see and enjoy “democracy dividends” – social welfare, justice, equity, and equal access to resources and power. A reflection on the above calls to question certain issues that stands as challenge(s) to democratic governance in Nepal. These issues remain critical governance problems: leadership challenges, corruption, lack of transparency, and system of electoral reforms, rising civil strife, poverty, unemployment, lack of human security and human rights.